Monday with a mad genius - Osborne, Mary Pope.; Murdocca, Sal. (New York : Random House, 2007)
Jack and Annie travel 500 years back in time to Florence, Italy, and spend a day helping Leonardo da Vinci in the hope of learning another secret of happiness.
"A Merlin Mission."
"A Stepping Stone book."
RL: 3.3.
Keywords: Leonardo, -- da Vinci, -- 1452-1519 -- Juvenile fiction; Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Curiosity -- Juvenile fiction; Florence (Italy) -- History -- 1421-1737 -- Juvenile fiction; Italy -- History -- 1492-1559 -- Juvenile fiction